2016
DOI: 10.1177/1059601116668763
|View full text |Cite
|
Sign up to set email alerts
|

Space Exploration Illuminates the Next Frontier for Teams Research

Abstract: Effective teamwork is beneficial for organizations on Earth, but is a sine qua non for teams venturing into outer space. The prospect of sending a team to Mars by the year 2030 invites organizational scientists to take stock of what we know and what we still need to know about teams. The team endeavoring to Mars will be multicultural and interdisciplinary, living and working in uncomfortable and dangerous conditions, and doing so in close collaboration with distant teams back on Earth. Tackling the teamwork ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 103 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…It has been noted, however, that IPO frameworks are also quite linear in their depiction of team functioning (Ilgen et al, 2005). In response to criticisms that neither model well represents the dynamic functioning of teams operating in complex environments (Mesmer-Magnus et al, 2016), Mathieu and colleagues (2017) presented a model in which inputs to team functioning, meditating mechanisms and structural factors are depicted as overlapping coevolving facets of teams that combine to generate outcomes. In this model structural features include task scope and complexity, team interdependence and virtuality.…”
Section: Example #1 -Team Coaching and Team Developmentmentioning
confidence: 99%
“…It has been noted, however, that IPO frameworks are also quite linear in their depiction of team functioning (Ilgen et al, 2005). In response to criticisms that neither model well represents the dynamic functioning of teams operating in complex environments (Mesmer-Magnus et al, 2016), Mathieu and colleagues (2017) presented a model in which inputs to team functioning, meditating mechanisms and structural factors are depicted as overlapping coevolving facets of teams that combine to generate outcomes. In this model structural features include task scope and complexity, team interdependence and virtuality.…”
Section: Example #1 -Team Coaching and Team Developmentmentioning
confidence: 99%
“…The project literature helps us understand the implications of this attention perspective within and across teams on individual and team behavior. This literature concedes that projects that focus on their sole effectiveness through pursuing their independent goals are often those that succeed (Martinsuo, 2013), because allegiances and misalignment of goals across teams may limit the effectiveness of MTM on any single project (Halevy & Cohen, 2019; Mesmer-Magnus, Carter, Asencio, & DeChurch, 2016). For example, a recent study demonstrated that when developers discuss multiple projects simultaneously, the average amount of time to resolve an issue declines; however, this discussion-switching can hurt the resolution time of a single project (Hu, Wang, Chang, Yin, & Zhang, 2018).…”
Section: Outcomes Of Mtmmentioning
confidence: 99%
“…This sense of urgency may be short- and/or long-lasting. For example, the timing of a space shuttle launch is sensitive in terms of managing numerous tasks simultaneously to ensure the launch occurs at precisely the right time, and then monitoring is rigorously conducted to ensure any crew needs are immediately addressed; similarly, landings often have a need for urgent and precise timing to ensure the crew is safely rescued (Mesmer-Magnus, Carter, Asencio, & DeChurch, 2016; Vessey, 2014).…”
Section: Question 1: Why Is It Important To Understand Teamwork In Mt...mentioning
confidence: 99%